Macrophages modulate fibrosis during newt lens regeneration - Georgios Tsissios; Anthony Sallese; J. Raul Perez-Estrada; Jared A. Tangeman; Weihao Chen; Byran Smucker; Sophia C. Ratvasky; Erika Grajales-Esquivel; Arielle Martinez; Kimberly J. Visser; Alberto Joven Araus; Hui Wang; et al. (Stem Cell Research & Therapy, 2024)
Abstract Background Previous studies have suggested that macrophages are present during lens regeneration in newts, but their role in the process is yet to be elucidated. Methods Here we generated a transgenic reporter line using the newt, Pleurodeles waltl, that traces macrophages during lens regeneration. Furthermore, we assessed early changes in gene expression during lens regeneration using two newt species, Notophthalmus viridescens and Pleurodeles waltl. Finally, we used clodronate liposomes to deplete macrophages during lens regeneration in both species and tested the effect of a subsequent secondary injury after macrophage recovery. Results Macrophage depletion abrogated lens regeneration, induced the formation of scar-like tissue, led to inflammation, decreased iris pigment epithelial cell (iPEC) proliferation, and increased rates of apoptosis in the eye. Some of these phenotypes persisted throughout the last observation period of 100 days and could be attenuated by exogenous FGF2 administration. A distinct transcript profile encoding acute inflammatory effectors was established for the dorsal iris. Reinjury of the newt eye alleviated the effects of macrophage depletion, including the resolution of scar-like tissue, and re-initiated the regeneration process. Conclusions Together, our findings highlight the importance of macrophages for facilitating a pro-regenerative environment in the newt eye by regulating fibrotic responses, modulating the overall inflammatory landscape, and maintaining the proper balance of early proliferation and late apoptosis of the iPECs.